Humanitarian compound of modernization of higher education in Ukraine - VLASENKO, FEDIR (Journal of Education, Technology and Computer Science, 2016)
The article observes the main tendencies of modernization of Ukrainian education. Determines the place of humanitarian education in determined process. Determines the role of humanitarian education in the training of modern competitive specialist. Outlines the trends of modern education in Ukraine.